Tajemnica zawodowa dotycząca działalności funduszy emerytalnych i jej ochrona karnoprawna - Płońska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The paper discusses the concept of professional secrecy concerning the pension funds activities and indicates the substance of its criminal law protection. The main thesis of this article is that in the age of intensive economic development, an information, especially professional secrecy, becomes a particularly important legal interest, which requires a far-reaching legal protection which is provided by criminal law provisions. The purpose of this paper is also the analysis of the legal consequences of committing a disclosure or use of professional secrecy offence under the Article 220 of The Organization and Operation of Pension Funds Act of August 28th, 1997. The scientific method used in this paper is a dogmatic analysis of law
Keywords: tajemnica zawodowa; fundusze emerytalne; przestępstwa; ustawa o funduszach emerytalnych (1997)